2017
DOI: 10.1186/s13045-017-0410-6
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic alterations of m6A regulators predict poorer survival in acute myeloid leukemia

Abstract: Methylation of N6 adenosine (m6A) is known to be important for diverse biological processes including gene expression control, translation of protein, and messenger RNA (mRNA) splicing. However, its role in the development of human cancers is poorly understood. By analyzing datasets from the Cancer Genome Atlas Research Network (TCGA) acute myeloid leukemia (AML) study, we discover that mutations and/or copy number variations of m6A regulatory genes are strongly associated with the presence of TP53 mutations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
172
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(185 citation statements)
references
References 10 publications
4
172
3
Order By: Relevance
“…The m 6 A modification is one of the most common and critical mRNA modifications in human malignant diseases . More and more evidences suggest that the “writers,” “erasers,” and “readers” of m 6 A exert important role in the cancer initiation and development . As the first identified “erasers” of m 6 A, FTO was showed associated with not only the increased body mass and obesity but also the progression of various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The m 6 A modification is one of the most common and critical mRNA modifications in human malignant diseases . More and more evidences suggest that the “writers,” “erasers,” and “readers” of m 6 A exert important role in the cancer initiation and development . As the first identified “erasers” of m 6 A, FTO was showed associated with not only the increased body mass and obesity but also the progression of various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that m 6 A modification is catalyzed by a methyltransferase complex consisting of “writers” proteins methyltransferase‐like 3 (METTL3) and METTL4, and “erasers” fat mass and obesity‐associated protein (FTO) and AlkB homolog 5 (ALKBH5) . Alternation of these component genes in the methyltransferase complex can give rise to a significant phenotype change, such as carcinogenesis . FTO, the first identified “eraser” of m 6 A, has been reported to play an oncogenic role in various types of cancer, including endometrial, breast, pancreatic cancer, and acute myeloid leukemia (AML), suggesting the functional importance of the mRNA m 6 A methylation and its modulators in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The mutations and CNVs of m 6 A regulatory genes were associated with poorer cytogenetic risk and other clinic‐pathological or molecular features in AML 85. In addition, impaired m 6 A regulatory genes were notably associated with the presence of TP53 mutations in AML patients and both might play a complementary role in the maintenance of AML 85. Collectively, it is unknown whether single alteration or multiple changes in m 6 A modification profoundly affect leukaemia.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%
“…It was reported that IGF2BP1 sustains the expression of various SRF target genes and promotes liver cancer progression in an m6A‐dependent manner . 2%–9% copy number variation (CNV) of m6A regulator genes, including METTL3 , METTL14 , YTHDF1 , YTHDF2 , ALKBH5 , and FTO , were observed in acute myeloid leukemia (AML), while patients carrying m6A‐related CNVs or mutations displayed poorer prognosis . Increased m6A enhances the expression of PTEN/c‑Myc/BCL2, modulates myeloid differentiation, haematopoietic stem/progenitor cell specification, while FTO‐mediated m6A inhibition promotes leukocyte transformation and leukemogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…17 2%-9% copy number variation (CNV) of m6A regulator genes, including METTL3, METTL14, YTHDF1, YTHDF2, ALKBH5, and FTO, were observed in acute myeloid leukemia (AML), while patients carrying m6A-related CNVs or mutations displayed poorer prognosis. 18 Increased m6A enhances the expression of PTEN/c-Myc/BCL2, modulates myeloid differentiation, haematopoietic stem/progenitor cell specification, while FTO-mediated m6A inhibition promotes leukocyte transformation and leukemogenesis. [19][20][21][22] Upregulation of ALKBH5 or knockdown of METTL3/METTL14 were also reported to induce glioblastoma tumorigenesis by promoting FOXM1 expression.…”
Section: Introductionmentioning
confidence: 99%